Association of central arterial stiffness with hippocampal blood flow and N-acetyl aspartate concentration in hypertensive adult Dahl salt sensitive rats. Issue 10 (October 2021) - Ajamu, Samuel O.; Fenner, Rachel C.; Grigorova, Yulia N.; Cezayirli, Defne; Morrell, Christopher H.; Lakatta, Edward G.; Bouhrara, Mustapha; Spencer, Richard G.; Fedorova, Olga V.; Fishbein, Kenneth W.
Abstract : Background: Central arterial stiffness (CAS) is associated with elevated arterial blood pressure (BP) and is likely associated with stiffening of cerebral artery walls, with attendant cerebral hypoperfusion, neuronal density loss and cognitive decline. Dahl salt-sensitive (Dahl-S) rats exhibit age-associated hypertension and memory loss, even on a normal salt intake. Method: We sought to explore whether central arterial pulse wave velocity (PWV), a marker of CAS, is associated with hippocampal cerebral blood flow (CBF) and neuronal density in hypertensive Dahl-S rats. We measured systolic BP (by tail-cuff plethysmography), aortic PWV (by echocardiography) and CBF and N -acetyl aspartate (NAA) (by magnetic resonance imaging) in 6 month-old male Dahl-S rats ( n = 12). Results: Greater PWV was significantly associated with lower CBF and lower NAA concentration in the hippocampus, supporting a role of CAS in cerebrovascular dysfunction and decline in cognitive performance with aging. Conclusion: These findings implicate increased CAS in cerebral hypoperfusion and loss of neuronal density and function in the Dahl-S model of age-associated cardiovascular dysfunction. Abstract : Supplemental Digital Content is available in the text